Stimulating Career Development: Assessment of the Effects of Guest Speaker Learning Experiences on Students Enrolled in Criminal Justice College Courses - Chintakrindi, Sriram (International Journal of Criminology and Sociology, 2023)
This research study examines the impact of a guest speaker intervention on college students enrolled in criminal justice courses at a mid-sized university in California. Students in the study attended guest speaker presentations ranging from probation officers, correctional officers, academics, and public defenders. Students in the study were required to complete a pre-and post-survey throughout the Fall 2022 and Spring 2023 semesters that examined the students’ agreeableness, confidence, and knowledge with regard to their experiences with attending guest speaker opportunities and their knowledge about career pathways and academic concepts while pursuing a college degree. The results from this study indicate that many students find guest speaker opportunities to be both beneficial for advancing their knowledge of the criminal justice system and confidence in pursuing a career in criminal justice.